Carnaval na República do Medo: ironia e paródia em letras de Gonzaguinha - um estudo bakhtiniano - Archanjo, Rafael Menari (2015)
History shows that the recurrence to comic is vehemently fought by totalitarian regimes. Such occurrence, considered as a manifestation of the carnival worldview, breaks the typical serious aspect of discourses in such periods, by means of the hidden polemic and parody. After the civil-military coup in 1964, the Brazilian government, considering the exception regime had been established, built an optimist-nationalist, civic and disciplinarian discourse of an emerging country benefited by the economical development, and the field of the song became a wide axiological arena; stage for dialogical and ideological clashes, in which the authorcreator Gonzaguinha became a staunch opposer to the regime. In the proposed investigation, we observed how, dialogically, the utterances of the song lyrics of the author-creator who appears in the work of the songwriter carnivalizated the discourse of the propaganda engendered by the Brazilian government. The heuristic exercise had, in Bakhtin’s (1987; 1997; 1998; 2011; 2012) and Bakhtin and Volochínov’s (1926; 2006) studies, its main reflections that, added to the contributions of other researchers, highlithing Hutcheon (1985), Brait (1996; 2003; 2005), Koch (2008), Fiorin (2009; 2012) and Marchezan (2012; 2015, unpublished), built the contribution basis. Other studies which had a relation with this investigation were also added to the theoretical framework. The proposal could be justified in the almost not existence of works in Linguistics applied to Gonzaguinha’s work, who is known for his lyrical productions. The analysis plan was based on a qualitative method of bibliographic review, along with the exegetic application of the theory. The observations were restricted to the lyrics of the six selected lyrics distributed in six albums of the artist that were launched between 1973 and 1981. By means of the analyses, we verified that the author-creator uses carnivalization to make a counter discourse to the government, using, to circumvent the government censorship, semantic ambiguities which have an ironic effect. The dialogical relations occur, but in opposition. The apparent “said” elements on the discourse of the author-creator are subverted by “unsaid” ones, which resound within the discourse, building their hidden reply. The same happens when the author-creator uses the parodic intertextuality. Both processes envolve the free cry of the carnival public square. The recurrence to parody and irony establishes the comic over seriousness, opening the semantic field of the song to the pluridiscursivity. Both processes, that, in certain recurrences, do not split up, allow bivocality, the reflexion of voices that collide axiologically, in the tense relation between the authoritarian word and the internally persuasive word. In this clash, the author-creator’s irony and parody deconstruct the meanings and symbols of the ufanist propaganda, constructing an utterance in collision with the univocality of the state discourse.